Answer:
c
Step-by-step explanation:
252 = 7 *36
36 = 6 *6 = 6²
a² -b² = (a + b)(a - b)
7h² - 252k² = 7(h² - 36k²)
= 7(h² - [6k]² )
= 7(h +6k)(h - 6k)
Answer:
C.
Step-by-step explanation:
{y = ¼x - 3}
{2x + 4y = 12
2x + 4[¼x - 3] = 12
2x + x - 12 = 12
3x - 12 = 12
+ 12 + 12
_________
3x = 24
__ __
3 3
[Plug this back into both equations above to get the y-coordinate of −1];
I am joyous to assist you anytime.
<span>Two cars start moving from the same point. one travels south at 48 mi/h and the other travels west at 20 mi/h. at what rate is the distance between the cars increasing four hours later? so its 400%</span>